Teachers' Performance in Integrating Technology in The Digital Era Through Professional Competence and Self-Efficacy - Sulistiani, Ika Ratih; Dewi, Mutiara Sari (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2024)
This study is to ascertain the impact of teachers in MIN 1 Malang City regarding technology professional knowledge, self-efficacy, and the efficacy of technology integration performance. It also seeks to ascertain the relationship between these variables. This study employs a quantitative methodology within the framework of a descriptive-explanatory research design. Based on teaching experience spanning more than five years, 103 teachers, or 45.5% of the total population, comprise the samples, as determined by the sample calculation using the Slovin formula. A questionnaire with a measurement scale ranging from 1 to 5 was the instrument utilized. Descriptive statistical analysis and structural equation modeling (SEM) were used as data analysis methodologies. Teacher Technology Professional Knowledge, Teacher Self-Efficacy, and Technology Integration Performance of MIN 1 Malang City Teachers meet high criteria with a PPT value of 3.87 (77.4%), EF of 3.54 (70.8%), and KIT of 3.53 (70.6%). The dimension of technology content knowledge, the dimension of confidence for students, and the dimension of ICT confidence have the greatest influence on each variable by providing the highest value on its indicators. There is an influence of technology professional knowledge on technology integration performance in learning through teacher self-efficacy in MIN 1 Malang City. It can be said that the higher the professional knowledge of technology and teacher self-efficacy, the more effective integrating technology is.